Swami Vivekananda - Srivastava, Kamal S; Srivastava, Sangeeta (New Delhi, 2011)
This book talks about lectures of Vivekanand, reading, Raja Yoga, Lectures and Discourses, writings, Poems & Letters.
Keywords: "Vivekananda, Swami-Biography"